The dialectic of the beginning in Hegel's science of logic: the Being-there (Dasein) as a result of the Being-nothing-becoming dialectic - Nicolau, Marcos Fabio Alexandre (Argumentos - Revista de Filosofia, 2010)
We will try to analyze the speculative development of being which is presented by Hegel in his exposition of the Doctrine of Being, specifically its first moment, Quality. All categories that constitute the development of being take place as an upshot of becoming, besides one could say that all philosophy as propounded by Hegel is a philosophy from process or from becoming. The first determining point of being, on its role of thought determined by its becoming, is quality; within which, as ruled by the dialectic principle found in the conflict between being and nothing, each moment from this development of being denies itself within itself. Dialectical movement leads from quality to quantity, and, afterwards, to measure, which is the trueness of quality and quantity, a unit within which all quantitative change indicates at the same time a qualitative change. Therefore, our proposal is to expound the category Determinate Being (Dasein) as an upshot from the process that was developed from the Doctrine of Being which by using the dialectical method directs its exact meaning and necessary bindings by means of which it grows into a true progressive determination of the being-in-itself, namely, the beginning of science.